Problems of formation and development prospects of small innovative business in Kazakhstan - Kozhabayeva, S.A.; Ukubassova, G.S.; Galiyeva , A.Kh. (BUKETOV BUSINESS REVIEW, 2019)
The article identifies the main problems of the development of innovative activity and activity of enterprises, as well as the innovative potential of industries of the Republic of Kazakhstan. The authors of the article analyzed the indicators characterizing enterprises and the number of employees involved in research and development. The authors highlighted the main reasons restraining the activity of enterprises in the field of new technologies: low level of demand of industrial enterprises for innovative technologies; lack of financial resources for innovative development; lack of highly qualified workers employed in high technology sectors; lack of motivation of economic entities in the implementation of innovations; the lack of focus on business development of innovative human capital. According to the authors, small innovative businesses have special advantages in introducing new technologies: adaptability to new requirements of technological progress; the ability to quickly diversify the specialization of production; flexibility in expanding the range of products. The article offers recommendations on the development of small innovative business in Kazakhstan: the use of a modern interactive approach; use of advanced technologies; attracting scientists to implement innovative projects; stimulation of innovative activity of small businesses; development of partnership mechanisms between the state, private business and society.